Dualisme Kompetensi Peradilan Permohonan Pengangkatan Anak Bagi Pemohon Yang Beragama Islam - Nugroho Noto Diharjo (Fakultas Syariah IAIN Ponorogo, 2021)
Abstract: The Child adoption application for Moslem applicants and Moslem adopted children potential are legal by the State court and the religion court in pratice, for this reason this matter causes the competency dualism in accepting, examining, and assigning that child adoption application. in the Mojokerto state court Decicion No.04/Pdt P/2012//PN Mkt, the Purwokerto faith courtroom Desicion No.a hundred thirty/Pdt P/2014/PA Pwt. the ones fourt courtsstate that they are legal to accept, examine and assign the adoption of children. according to the research, by way of yuridis normative approch sesult of the child adoption application proposed by means of Moslem applicants, both in the religion court and trough the state court have the authority to just accept, have a look at, grant, and assign the child adoption application, but with different legal consideration. inside the state court decision, the judicial legal consideration refers back to the common legislation law such as the child Protrction laws, the population Administrations law, the Goverment Ordinance, and the supreme court circular, however, the religious court in based on the Islamic law compilation. The legal consequences caused by child adoption decision carried out inside the state court, the adopted kids have inheritance rights from the adoptive mother and father, at the same time as in the religious Courts, the adoyed children do not server ties with the biological parents. consequently the adopted children do not inherit property from the adoptive mother and father.